Cytoprotective effect of crocin and trans-resveratrol on photodamaged primary human retinal pigment epithelial cells. Issue 2 (March 2021) - Kassumeh, Stefan; Wertheimer, Christian M; Ohlmann, Andreas; Priglinger, Siegfried G; Wolf, Armin
Purpose: Light-induced damage to retinal pigment epithelium during pars plana vitrectomy remains a hot topic in ophthalmology. Improvements in technology led to a change of light sources, selective filters, and shorter light exposure time. Currently, there is no satisfying solution to the problem. The aim of the study was to investigate the cytoprotective effects of crocin and resveratrol on light-induced damage to primary human retinal pigment epithelial cells in vitro . Methods: Primary human retinal pigment epithelial cells were exposed to light analogous to the illumination during pars plana vitrectomy. To evaluate the cytoprotective effects and potential toxicity of resveratrol and crocin, human retinal pigment epithelial cells were incubated with varying concentrations of both before 3-[4, 5-dimethylthiazol-2-yl] tetrazolium bromide (MTT) viability assay. Furthermore, glutathione levels were measured to investigate synergistic antioxidant potential. Apoptosis of human retinal pigment epithelial cells was determined by a nucleosome detection enzyme-linked immunosorbent assay. Results: Crocin and resveratrol improved cell viability in photodamaged human retinal pigment epithelial cells significantly from 40.65 ± 21.99% in illuminated human retinal pigment epithelial cells and reached a peak viability of 85.64 ± 11.37% in crocin and resveratrol pretreated cells (for all: p < 0.001). In line, the combination of the supplements increased glutathione levels significantly from 39.35 ± 21.96% to 80.74 ± 10.32% ( p = 0.017). No toxic effects were detected ( p > 0.99). However, no change in apoptosis rates could be observed following pretreatment with crocin and resveratrol ( p > 0.99). Conclusion: Crocin and trans-resveratrol revealed cytoprotective effects on human retinal pigment epithelial cells supporting both supplement's development as potential perioperative treatments in light-induced retinal pigment epithelial damage.